2016
DOI: 10.1007/s11090-016-9769-3
|View full text |Cite
|
Sign up to set email alerts
|

Polytetrafluoroethylene Sputtered PES Membranes for Membrane Distillation: Influence of RF Magnetron Sputtering Conditions

Abstract: Thin films of fluorocarbon were deposited on polyethersulfone membranes via argon plasma sputtering of a poly (tetrafluoroethylene) (PTFE) target in an RF magnetron plasma reactor. The obtained deposited ultrathin coatings had nanoscale roughnesses and high degrees of fluorination.The intensity of fluorine atom in plasma environment during fluorocarbon deposition was investigated. Depending on the deposition conditions comprising working gas pressure, applied RF power, and distance between the target and the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Further, the redeposition of the fluorocarbon species from the sacrificial PTFE disc onto the sample also contributes to the formation of C−CF x and CF bonds on the surface. [24,44,45] Also, energetic Ar ion irradiation breaks the polymer chain and creates lots of free radicals. Hence, when the surface is exposed to an ambient environment, the O/C ratio increases from 0.02 to 0.3 due to the post-plasma auto-oxidation of polymer fragments created on the surface after plasma treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the redeposition of the fluorocarbon species from the sacrificial PTFE disc onto the sample also contributes to the formation of C−CF x and CF bonds on the surface. [24,44,45] Also, energetic Ar ion irradiation breaks the polymer chain and creates lots of free radicals. Hence, when the surface is exposed to an ambient environment, the O/C ratio increases from 0.02 to 0.3 due to the post-plasma auto-oxidation of polymer fragments created on the surface after plasma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Even though PTFE is chemically inert, when exposed to the various gaseous plasma, apart from the morphological changes, severe chemical composition changes are also taken place on the surface. Depending upon the feed gas, several chemical changes such as defluorination, [19,20] chain scission, [21] crosslinking, [22][23][24][25] and post-plasma auto-oxidation [26] are reported by various research groups. For instance, Vesel et al [20] studied the defluorination of PTFE using hydrogen plasma and found that the F/C ratio decreased from 2.0 to 0.2.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Yang et al [64] were able to obtain a superhydrophobic PVDF membrane exhibiting a contact angle of 162.4 • by CF 4 plasma treatment. Pedram et al [65] designed thin films of fluorocarbon which were deposited on PES membranes through argon plasma sputtering of PTFE targeted in RF magnetron plasma reactor. Recently, Woo et al [66] prepared PVDF membrane via electrospinning and treated the surface with CF 4 plasma.…”
Section: Surface Engineeringmentioning
confidence: 99%
“…This approach provides membranologists with the freedom to independently design and optimize the layers while the self-termination of IP led to ultrathin skin that is <200 nm [8,9]. Apart from IP, many techniques such as dip-coating [10], spin-coating [11], layer-by-layer [12,13], grafting [14], chemical vapor deposition [15], surface growth/crystallization [16,17] and sputter-coating [17,18] have been devised for the fabrication of TFC. A polymeric membrane with anisotropic structure continues to be the model for many commercial membranes available today.…”
Section: Introductionmentioning
confidence: 99%